2019
DOI: 10.1177/0894439319896230
|View full text |Cite
|
Sign up to set email alerts
|

Technological Addiction in Context: The Influence of Perceived Neighborhood Social Disorder on the Extensive Use and Addiction to the Smartphone

Abstract: After more than a decade of research on smartphone addiction, there is currently empirical evidence on the main sociodemographic, psychological, and psychosocial correlates of this type of behavioral addiction. However, research in this field has not yet paid sufficient attention to the influence that the social context may have on smartphone addiction, an aspect that has been frequently pointed out by investigations on both substance and behavioral addictions. The objective of this research was to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Studies in social ecology have documented the effect of neighborhood social disorder on behavioral addictions, and recent empirical evidence indicates that living in socially disordered neighborhoods is associated with higher levels of smartphone addiction (see Herrero, Torres, et al, 2019b, for an analysis). These socially disordered neighborhoods can generate stressful situations that residents may want to avoid by becoming isolated from community life.…”
Section: Social Antecedents Of Sdpmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in social ecology have documented the effect of neighborhood social disorder on behavioral addictions, and recent empirical evidence indicates that living in socially disordered neighborhoods is associated with higher levels of smartphone addiction (see Herrero, Torres, et al, 2019b, for an analysis). These socially disordered neighborhoods can generate stressful situations that residents may want to avoid by becoming isolated from community life.…”
Section: Social Antecedents Of Sdpmentioning
confidence: 99%
“…At this point, an overuse and even a technological dependence of the smartphone could be observed. The constant need for digital social inclusion of the smartphone users of these disadvantaged environments could be associated with high SDP, which can potentially lead to smartphone addiction (Herrero, Torres, et al, 2019b). A positive relationship will therefore be expected between neighborhood social disorder and SDP.…”
Section: Social Antecedents Of Sdpmentioning
confidence: 99%
“…Victimización por ciberdelincuencia Modelos de mixtura de crecimiento latente Adicción a los teléfonos inteligentes Apoyo social Curvas de supervivencia Studies on smartphone addiction have recently identified some psychosocial vulnerabilities in addicted users that might be related to a higher propensity to be victimized by cybercrime. Longitudinal (Herrero, Torres, Vivas, & Urueña, 2019a;Herrero, Urueña, et al, 2019b;Lapierre & Zhao, 2021) and correlational research findings (Al-Kandari, & Al-Sejari, 2020;Ranney & Troop-Gordon, 2020) have suggested that smartphone-addicted users may have problems with social relationships in their daily lives (e.g., poor social support) compared to non-addicted users. While both smartphone addiction and social support have been linked primarily to subjective well-being and health, their relationship to cybercrime victimization has also been found in different studies (Judges, et al, 2018;Martínez-Ferrer et al, 2021;Mollenhorst, et al, 2018;Oksanen, & Keipi, 2013;Xing, et al, 2020).…”
Section: Palabras Clavementioning
confidence: 99%
“…[8][9][10][11][12][13] Although it is widely acknowledged that social environment serves as both a risk and protective factor for the initiation, treatment, and prevention of addictive behaviors, 14 there remains insufficient attention to the social factors associated with smartphone dependence. 15 Currently, research mainly revolves around risk indicators, such as neighborhood social disorder, social digital pressures, and various life stress. [15][16][17][18] How university students perceive the social environment they live in (eg, social mobility) has been found to play a crucial role in shaping behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…15 Currently, research mainly revolves around risk indicators, such as neighborhood social disorder, social digital pressures, and various life stress. [15][16][17][18] How university students perceive the social environment they live in (eg, social mobility) has been found to play a crucial role in shaping behaviors. 19,20 When individuals perceive high rather than low social mobility, they tend to have stronger selfmotivation ability and participate in more adaptive behaviors conducive to the future.…”
Section: Introductionmentioning
confidence: 99%